EFFECTS OF HEGU POINT SUPPRESSOR (LI 4) AND BIRTH BALL TECHNIQUE ON LABOR PAIN: A REVIEW - Dina Anggraini; Triana Sri Hardjanti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Pain in labor is the cause of fear, anxiety and childbirth trauma among pregnant women so that it affects the health condition of the mother and the fetus. Non-pharmacological methods such as pressing the hegu point (LI 4) and birth ball technique are believed in reducing the intensity of labor pain without side effects. This study aims to analyze the effect of pressing hegu point (LI 4) and technique birth ball on labor pain.Methods: This was a literature review using PRISMA-P (Preferred Reporting Items for Systemic Review and Meta-Analysis Protocols) to identify all published articles with ‘point hegu (L1 4)’, ‘birth ball’, and ‘labor pain’ as the keywords. Electronic databases such as Google Scholar and Science Direct were used in searching the articles that were published between 2011 and 2019. Other criteria were articles that used experimental research design and written in English and Indonesian language.Results: There were 18,072 articles recorded, of which 10 articles were included in the systematic review. By pressing hegu points (LI 4) for 20 minutes to 240 minutes, it helped mothers to reduce labor pain. Sitting on a birth ball by wiggling the pelvis relieved the labor pain, improved the self-control, as well as felt satisfied with birth experiences. Conclusion: Methods of pressing hegu points (LI 4) and birth ball techniques can effectively reduce the intensity of labor pain. Further study can be conducted using other keywords and methods.